The Empirical and Dynamic Relationship between Sectoral Output, Capital Formation, and Per Capita Income in Nepal - Parajuli, Pabita (Journal of Multidisciplinary Research Advancements, 2025)
This study investigates the relationship between key economic sectors, capital formation, and per capita income in Nepal. Focusing on the period from 1975 to 2023, it has two central objectives: (ii) to show the empirical relationship between gross capital formation, primary and tertiary sectors on real per capita output, and (iii) to explore the short-run and long-run relationship between these variables. Using time-series data and employing the Johansen cointegration test and the Vector Error Correction Model (VECM), the analysis confirms a significant long-run relationship. The results reveal statistically significant impacts of the primary sector, the tertiary sector, and gross capital formation on real per capita income in both the short and long run. The Error Correction Term was -0.28 and significant, indicating a 28% annual adjustment towards long-run equilibrium. The study concludes that primary and tertiary sector outputs, along with capital formation, are fundamental to Nepal's per capita income, with significant implications for economic policy.